The Effect of Social Support and Visual Content of Food Vloggers in Influencing Consumer Trust and Attitudes towards Purchase Intention through Social Media - Sari, Delia Tridayana; Lilik Wahyudi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to examine the effect of information support, emotional support, and influencer credibility on consumer trust and consumer attitudes. In addition, it also examines the effect of consumer trust and attitudes on consumer purchase intentions. In the digital age, social media such as Facebook, YouTube, Instagram, Twitter, and TikTok greatly influence consumer purchasing decisions. In Indonesia, there are 63 million internet users, many of whom use social media. Visual content from food vloggers builds trust, and social support increases consumer purchase intention. Influencer credibility and positive interactions are also important in purchasing decisions. This research design uses a cross-sectional approach and quantitative methods. The study aims to analyze the relationship of information support, emotional support, and influencer credibility on consumer purchase intention in Indonesia. Data obtained from surveys on social media. The results of hypothesis testing show that Attitude affects Purchase Intention with a t-test value of 5. 0001. Emotional Support also affects Attitude and Trust, with a t-test of 6. 0528 and 5. 0752 respectively. Informational Support affects Attitude and Trust with t-test values of 5. 1194 and 3. 8635. Influencer Credibility has a significant effect on Attitude and Trust, with t-tests of 6. 2586 and 5. 3135 respectively. Finally, Trust affects Purchase Intention with a t-test value of 5. 7274. All hypotheses are accepted.